Current integrated pest management tactics for the spotted wing Drosophila and their practical implementation in Switzerland - Baroffio, Catherine A.; Dorsaz, Mélanie; Kuonen, Fabio (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae), the spotted wing Drosophila (SWD) is a concern for small fruit and stone fruit growers. This invasive pest lays eggs in healthy fruits with a serrated ovipositor, resulting in considerable economic losses, mainly in berry crops. In Europe, it was first recorded in Switzerland in 2011, causing considerable damage in all small fruit crops, especially in later-developing crops (autumn raspberries, blackberries, blueberries and elderberries). The pest was found in all regions of the country, from low altitudes to the timberline. The range of host plants is very broad, not only affecting crops, but also wild fruits. Switzerland has implemented a strategy at the national level by combining an effective monitoring system with hygiene measures and mass trapping. Insecticide applications, usually based on spinosyns, are only considered as a last resort. In addition to this already operative strategy, innovative alternatives are considered, in particular the use of repellents or masking substances.